Financial Health Analysis and Bankruptcy Prediction of BUMN Karya Listed on IDX in The Midst of Increasing Government Infrastructure Projects Based on The National Medium-Term Development Planning (RPJMN 2020 - 2024) - Akila Badzlina Putri; Ana Noveria; Oktofa Yudha Sudrajad (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
Concerning the increase in the national infrastructure budget by 6% from the previous year, as well as the emphasis on infrastructure reflected in the RPJMN 2020 – 2024 document, the government has once again appointed construction State-Owned Enterprises (BUMN Karya) as the drivers of national development. Unfortunately, over the past five years, the financial condition of BUMN Karya has deteriorated. Additionally, several directors within these companies have been implicated in corruption cases, damaging the public image and trust in BUMN Karya. This led the IDX to suspend trading in one of its stocks in May 2023. This study aims to evaluate the financial performance and health condition of BUMN Karya listed on the IDX, namely WSKT, WIKA, PTPP, and ADHI. The research methodology is based on the Ministry of SOEs No decree. KEP-100/MBU/2002. Furthermore, this study predicts the financial distress faced by these BUMN Karya from 2019 to 2023 using four methods: Altman Z-Score, Ohlson O-Score, Zmijewski, and Springate The findings indicate the health conditions of each company from 2019 to 2023 as follows: WSKT (BB, CCC, B, BB, B), WIKA (AA, BB, BB, B, CCC), PTPP (BBB, BB, BBB, B), and ADHI (BBB, B, BB, BB, BBB). Among the four predictive methods, the Altman Z-Score model most closely approximates the actual condition in 2024 with an accuracy rate of 65%. The results show that all four SOEs experienced a decline in their Altman Z-Score in 2023. This study complements previous research with a different approach and provides additional insights into the government’s push for infrastructure development and efforts to improve and strengthen the financial condition of BUMN Karya.